LAYANAN JASA DAN STRATEGI PEMBIAYAAN PADA MASA PANDEMI COVID DI PT. PEGADAIAN SYARIAH CABANG JAMBI - Muhammad Subhan; Agustina Agustina (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2023)
This study aims to determine the services during the pandemic, and the Financing Strategy carried out at PT. Jambi Branch of the Sharia Pawnshop. The objectives include the state of Service Services during the pandemic and the Financing Strategy at PT. Jambi Branch of the Sharia Pawnshop. This study uses a qualitative approach with data collection methods by conducting observations, interviews, documentation, and concluding: 1) In the services carried out during the Covid period at PT. Pegadaian Syariah Jambi Branch, namely: a) The service has slightly changed both inside and outside the outlet to prevent the transmission of covid-19. b) Those who can usually meet face-to-face with customers during the covid period must be isolated or online. c) Service PT. Sharia pawnshops can also be seen from the changes in employees who usually work directly in the office, and some work WFH (Work From Home. 2) In the financing strategy carried out by PT. Pegadaian Syariah Jambi Branch during the pandemic is as follows: a) Updating the way the sales business used to be less, now more on social media and digital applications. b) discounts for customers who purchase gold or use specific products at sharia pawnshops. c) For the micro during the pandemic, there is an easing for the businesses of affected customers by providing subsidies for MSMEs from the government. d) PT. Pegadaian Syariah Jambi branch conducted socialization to encourage customers to use digital pawnshops for house transactions.